Effect of interference study on carrageenan detection using ultraviolet visible spectrophotometry - Muhamad Eqmal Izman Mohd Fadli; Wan Elina Faradilla Wan Khalid; Sharina Abu Hanifah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Carrageenan is one of the most prominent hydrocolloids in the food industry used as a thickener and additive to improve the texture of food products. However, the detection of carrageenan in the food product is still limited as many interferences in the food matrix can interfere with the signal obtained. This research aims to study the effect of interference species on a simple and rapid quantitative detection of carrageenan by using a cationic dye which is methylene blue. Methylene blue will form a complex with carrageenan at 565 nm due to the hypsochromic shift of the methylene blue peak at 664 nm with a color change from blue to bluish purple. The optimization and analytical performance of carrageenan-methylene blue complexes were characterized by using UV-Visible Spectrophotometer. A dynamic linear concentration range for carrageenan detection was obtained in the range of 70-100 ppm (R2 = 0.9837) with a limit of detection (LOD) estimated at 38.37 ppm. The reproducibility study was found to give a satisfactory relative standard deviation (RSD) value of 1.64-1.94%. Selectivity experiments were carried out where the methylene blue demonstrated acceptable selectivity towards carrageenan with no significant interference from sucrose and glucose.